ANALISIS MAKNA PADA PUISI “SUKMA PUJANGGA” KARYA J.E TATENGKENG - Errika Anandita (Concept: Journal of Social Humanities and Education, 2022)
This study aims to analyze the meaning of several dictions in a text that deals with it. The source of the data used in this study in the text of a poem entiled Sukma Pujangga by J.E Tatengkeng. The aspect that must be investigated is analyzing the meaning of the 6 dictions in the poetry text of Sukma Pujangga. The method used in this research is descriptive qualitative. The results showed that from several dictions that have been analyzed, it can be seen from the meaning of the poem that it describes someone who has a very high artistic spirit and is willing to make any effort to maintain his desires and stance. He doesn’t want to live for other people and just wants to be free to do whatever he wants and achieve his dreams even though he has to go through various obstacles. There are several meanings contained in the poem, including: connotative meaning, contextual meaning, abstract words, and special words.